Computer networks - Tanenbaum, Andrew S. (Upper Saddle River, NJ : Prentice Hall PTR, 2003)
The book is an introduction to today's networks. The book has been thoroughly updated to reflect the newest and most important networking technologies with special emphasis on wireless networking, including 802.11 etc.
Includes bibliographical references (p. 835-868) and index.
rua 19/09/14
Loans
Keywords: Computer networks; Wireless networking